Preliminary Survey of the Occurrence of Entomopathogenic Nematodes and Fungi in the Forest Soils of Algeria (Silva Lusitana, 2011)
The natural distribution and diversity of entomopathogenic nematodes (EPN) and fungi (EPF) in various biotopes in Algeria was studied, particularly in forests and plantations of cedar, oak, pine, eucalyptus and palm. The objective of this study was to identify EPN and/or EPF species which could be used to control forest insect pests. Soil sampling was carried out at 223 sites from April 2007 to March 2008. To trap EPN's juvenile larvae of Steinernematidae and Heterorhabditidae and EPF, the method of "insect-trap" was used in the laboratory. Caterpillars of Galleria mellonella (Lep., Pyralidae) and the forest insects Thaumetopoea pityocampa (Lep., Thaumetopoeidae) and Lymantria dispar (Lep. Lymantriidae) were used. The presence of EPN was noted in 8.1% of the sampled sites and EPF in 9.9%. The presence of the EPN in the oasis biotope may result from particular microclimate conditions (of temperature and humidity). Nematodes belonging to the Steinernematidae family and Steinernema genus were identified. In addition, 10 fungal species were isolated, namely:Beauveria bassiana, Fusarium sp., Alternaria sp., Penicellium sp., Trichoderma sp., Sordaria sp., Mucor sp., Chaetomium globosum, Aspergillus nigricans and Rhizopus nigricans. The majority of the fungi were isolated in the conidian form, except for Chaetomium globosum which had its perfect form with perithecia. The presence of EPN and EPF seems to depend on the dominant species of forest trees, either cork oak (35%), cedar (12.5%), pine (12.5%), palm (10%) or eucalyptus (7.5%).